2015
DOI: 10.1111/mec.13142
|View full text |Cite
|
Sign up to set email alerts
|

Heterozygote deficits in cyst plant‐parasitic nematodes: possible causes and consequences

Abstract: Deviations of genotypic frequencies from Hardy-Weinberg equilibrium (HWE) expectations could reveal important aspects of the biology of populations. Deviations from HWE due to heterozygote deficits have been recorded for three plant-parasitic nematode species. However, it has never been determined whether the observed deficits were due (i) to the presence of null alleles, (ii) to a high level of consanguinity and/or (iii) to a Wahlund effect. The aim of the present work was, while taking into the possible conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 53 publications
4
35
0
Order By: Relevance
“…The life cycle of H. schachtii and the low dispersal ability of larvae result in inbreeding and/or substructuring (Wahlund effect), which leads to an increase of heterozygote deficiencies over time (Plantard and Porte ; Montarry et al. ). However, this increase in heterozygote deficiencies is possible only in populations that produce new generations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The life cycle of H. schachtii and the low dispersal ability of larvae result in inbreeding and/or substructuring (Wahlund effect), which leads to an increase of heterozygote deficiencies over time (Plantard and Porte ; Montarry et al. ). However, this increase in heterozygote deficiencies is possible only in populations that produce new generations.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study conducted both on field and wild populations suggested that HW departures also may be explained by genetic substructuring due to Wahlund effects at the scale of the host plant (Montarry et al. ).…”
Section: Methodsmentioning
confidence: 99%
“…Small effective sizes are one consequence of limited gene flow among populations and support the hypothesis that H. schachtii is a species constituted of genetically disconnected populations in the wild, even at very small spatial scale. Interestingly, a recent study documented a Wahlund effect in some wild H. schachtii populations sampled at the host scale, suggesting that active dispersal of this species can also be extremely limited even between subpopulations that occupy the same host plant (Montarry et al., ). These subpopulations may thus correspond to the smallest genetic unit at which individuals interbreed, that is the actual boundaries of populations in H. schachtii (Waples & Gaggiotti, ).…”
Section: Discussionmentioning
confidence: 99%
“…Field populations of H. schachtii have a similar substructuring patterns than wild populations, suggesting that active dispersal capabilities of nematodes are equivalent in wild and field conditions (Montarry et al., ). By contrast, in agrosystems, low genetic differentiation suggests that nematode populations are connected through gene flow among fields separated by distances that reach 150 km.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation